Pertimbangan Hukum Hakim Terhadap Kasus Penelantaran Dalam Rumah Tangga - Edwin C Risakotta; Margie Gladies Sopacua; Leonie Lokollo (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The judge's consideration of domestic neglect cases is very important considering that domestic neglect is part of domestic violence.Purposes of the Research: The purpose of this study aims to examine what is the basis for the judge's legal considerations for household investigation cases in the study of decision No. 120/Pid.Sus/2021/PN Amb and review and explain whether the crime given by the judge has had a deterrent effect on the perpetrator.Methods of the Research: The author uses Normative Juridical legal research which obtains data from literature studies in the form of laws, documents, books, magazines and other literature related to writing. Results of the Research: The results of this research show that the Ambon District Court judges in sentencing the perpetrators of domestic neglect crimes, the judges consider juridically, sociologically, and philosophically. Thus, the sanctions given by the judge to the perpetrator of the criminal act of domestic abuse have not had a deterrent effect, because the judge in making decisions considers more of the things that relieve the offender.